Effect of Nanoscale Zero-Valent Iron on Arsenic Bioaccessibility and Bioavailability in Soil - Chen, Shuo; Han, Lei; Wang, Qiu; Liu, Chenglang; Liu, Yuzhen; Li, Jie (Frontiers in Chemistry, 2022)
Hand-to-mouth activity is considered to be the main way for children to come into contact with contaminated soil, and bioavailability is an important factor affecting their health risk. To reduce soil As risk to human by oral exposure, nanometer zero-valent iron (nZVI) has been extensively studied for immobilising As contaminated soils, but its efficiency has not been investigated using in vitro assay and its influence on As-RBA. In this study, two contaminated soil (A and B) were amended with 1% and 2% (w/w) nZVI for 56d to study its effect on As fraction by sequence extraction, As bioaccessibility by SBRC assay, and As relative bioavailability (RBA) by mouse liver and kidneys model. Based on the sequence extraction, the As associated with the E1 (exchangeable fraction) and C2 (carbonate fraction) fractions were decreased from 3.00% to1.68% for soil A and from 21.6% to 7.86% for soil B after 2% nZVI treated for 56d. When assessing As bioaccessibility in all soils treated with nZVI by SBRC assay, it was found that As bioaccessibility was significantly higher in gastric phase (GP) and lower in intestinal phase (IP) (P<0.05), and the bioaccessible Fe concentration decreased significantly from gastric to intestinal phase at the same time. Based on the mouse liver-kidney model, the As-RBA in soil A increased from 21.6% to 22.3% and 39.9%, but in soil B decreased from 73.0% to 55.3% and 68.9%. In addition, there was significant difference between As bioaccessibility based on GP or IP of SBRC assay and As-RBA in two soils after treated with nZVI for 56d. To accurately assess the nZVI human health risk, As-RBA should be considered in concert with secondary evidence provided through fraction and bioaccessibility assessments. In addition, it is necessary to develop suitable in vitro assay to predict As-RBA in nZVI-amended soils.